Nutritional value of tifton 85 bermudagrass at two cutting heights and different times of storage - Sunahara, Samantha Mariana Monteiro; Neres, Marcela Abbado; Sarto, Jaqueline Rocha Wobeto [UNESP]; Nath, Caroline Daiane; Scheidt, Kácia Carine; Kuhn, Odair José (Universidade Estadual de Londrina, 2017)
The goal of this study was to assess the dehydration curve and nutritional value of Tifton 85 bermudagrass at two cutting heights from ground level (4 and 8 cm) during 120 days of storage in a closed shed. The dehydration curve was determined using samples from the entire plant at eight different times. The experimental design consisted of randomized blocks with plots subdivided per times and fve replicates. The second step consisted of assessing the nutritional value of the stored Tifton 85 bermudagrass in randomized blocks with plots subdivided per times and two treatments per plot: cutting height of four and eight centimeters from the ground, and fve different times for the subplots, with fve replicates. Dehydration of Tifton 85 bermudagrass at the two heights occurred in 48 hours, considered an ideal time for hay drying. The dry matter content responded quadratically to the time of storage of the two heights, only differing during baling and after 120 days of storage. Crude protein content had a quadratic behavior in the two cutting heights, with the smallest value after 30 days of storage (107.0 g kg-1) and the largest after 90 days (147.8 g kg-1) in the cutting height of eight centimeters. The ether extract exhibited a quadratic behavior in the two cutting heights, only differing after 90 days of storage. The neutral detergent fber content had linear positive response according to the time of storage, with no difference between the cutting heights. For the neutral detergent fber content in the two cutting heights, the quadratic regression model was the best ft to the data, differing between the heights after 30 and 60 days of storage. In vitro dry matter digestibility and in vitro cell wall digestibility values of the stored hay were lower than the values obtained at the time of cutting. Cutting performed at four centimeters from the ground was the most suitable for hay production due to higher dry matter production and nutritional value without difference between bailing treatments. Hay storage caused undesirable changes in the nutritional value, especially in fber content and in vitro digestibility.
Keywords: Bromatological composition; Cynodon spp; Dehydration